Community Based Support for People at Risk for Suicide and Those Who Care for them – Areas for Improvement. Issue 2 (2nd April 2020) - Finlayson-Short, Laura; Hetrick, Sarah; Krysinska, Karolina; Harris, Meredith; Salom, Caroline; Stefanac, Nina; Bailey, Eleanor; Robinson, Jo
Abstract : To systematically review the quality of evidence regarding the effectiveness of supports for people affected by suicide. EMBASE, MEDLINE, and PsychINFO were searched for evaluations of community-based supports for people affected by suicide. Outcomes included suicide-related behavior, depression, grief, quality of life, caring ability, and qualitative experiences. Fifteen studies evaluated 15 supports of various modalities. Study quality was generally poor; most studies examined bereaved individuals with mixed findings. Few reduced suicide-related behavior, half improved depression, and grief, while studies of caring ability, quality of life, or qualitative experiences reported positive effects. Supports associated with better outcomes connected peers with similar experiences, were provided over a period of months, and involved veteran rather than novice facilitators. Supports for people affected by suicide may be effective for improving suicide-related behavior, psychological adjustment, quality of life and caregiving, but require further evaluation.